CRIMINAL RESPONSIBILITY FOR MARINE POLLUTION MANAGEMENT IN A LEGAL PERSPECTIVE - Makmur Farhan Fahrezi Hrp; R. Juli Moertiono (Inspiring Law Journal, 2026)
Marine pollution is one of the environmental problems that has a serious impact on marine ecosystems, human health, and the survival of other living things. In the legal context, marine pollution is not only an environmental issue, but also an unlawful act that can be subject to criminal sanctions. This study aims to analyze the form of criminal responsibility for the perpetrators of marine pollution and the effectiveness of criminal law enforcement in efforts to overcome it.Using a normative juridical approach, this study refers to national laws and regulations such as Law Number 32 of 2009 concerning Environmental Protection and Management as well as relevant international legal instruments.The results of the study show that criminal liability can be imposed on both individuals and corporations that are proven to have committed marine pollution, with sanctions in the form of imprisonment, fines, and/or administrative actions. However, the implementation of law enforcement still faces various obstacles, including weak supervision, lack of coordination between agencies, and low legal awareness. Therefore, it is necessary to strengthen regulations, consistent law enforcement, and synergy between stakeholders in order to create effective legal protection for the marine environment.